Limited Effect of Future Land‐Use Changes on Human Heat Stress and Labor Capacity - Steven J. DeHertog; Anton Orlov; Felix Havermann; Suqi Guo; Iris Manola; Julia Pongratz; Quentin Lejeune; Carl‐Friedrich Schleussner; Inga Menke; Florian Humpenöder; Alexander Popp; Peter Lawrence; et al. (Earth's Future)
Abstract To achieve the 1.5°C target of the Paris agreement, rapid, sustained, and deep emission reductions are required, which often includes negative emissions through land‐based mitigation. However, the effects of future land‐use change on climate are often not considered when quantifying the climate‐induced impacts on human heat stress and labor capacity. By conducting simulations with three fully coupled Earth System Models, we project the effects of land‐use change on heat stress and outdoor labor capacity for two contrasting future land‐use scenarios under high‐ambition mitigation. Achieving a sustainable land‐use scenario with increasing global forest cover instead of an inequality scenario with decreasing forest cover in the Global South causes a global cooling ranging between 0.09°C and 0.35°C across the Earth System Models. However, the effects on human heat stress are less strong, especially over the regions of intense land‐use change such as the tropics, where biogeophysical effects on near‐surface specific humidity and wind speed counteract the cooling effect under warm extremes. The corresponding influence on outdoor labor capacity is small and inconsistent across the three Earth System Models. These results clearly highlight the importance of land‐use change scenarios for achieving global temperature targets while questioning the adaptation potential for reduction in heat stress.